Valuation of labour market entrance positions among (future) apprentices - Results from two discrete choice experiments. (December 2019) - Möser, Sara; Glauser, David; Becker, Rolf
Abstract: In this paper, we estimate the relative value of different employment characteristics when choosing between apprenticeship and job offers. Further, we test assumptions derived from sociological rational choice theory on preference heterogeneity by individual and context characteristics. For this purpose, we analyse data from two discrete choice experiments, one focusing on the choice of an apprenticeship position and the other on the choice of first employment position after vocational training. The experiments were conducted as part of the DAB panel study on educational and occupational trajectories of adolescents in German-speaking Switzerland on students respectively one year prior to leaving compulsory school, and during vocational training. Our findings show that the most relevant aspect when choosing a labour market entrance position is, that the job should match the desired occupational specialisation. Furthermore, considerable preference heterogeneity is found, which can partly be accounted for by individual- and labour market-specific subjective utility.